Hepatocellular carcinoma in Australia 1982‐2014: Increasing incidence and improving survival. (5th November 2018) - Wallace, Michael C.; Preen, David B.; Short, Mark W.; Adams, Leon A.; Jeffrey, Gary P.
Abstract: Background & Aims: There is a paucity of accurate and current data on hepatocellular carcinoma (HCC) trends in incidence and survival in developed countries. We performed an Australia‐wide assessment of HCC epidemiology across a 33‐year time span aiming to accurately describe changes in incidence and survival. Methods: Cases of HCC from 1982 to 2014 were identified via the Australian Cancer Database (ACD). Trends in incidence rates were explored using piecewise linear regression. Survival was compared by Kaplan‐Meier survival curves and 1‐, 3‐ and 5‐year survival probabilities by year of diagnosis. Results: Age‐adjusted HCC incidence rate increased from 1.38 per 100 000 (95% CI: 1.34‐1.43) in 1982 to 4.96 per 100 000 (95% CI: 4.89‐5.03, P  < 0.001) in 2014 with an average annual percentage increase of 4.46% (95% CI: 4.24%‐4.69%). The highest incidence rate in 2014 was in those aged 75‐79 (24.31 per 100 000; 95% CI: 19.50‐29.12). Almost 80% of cases across the period were men who had significantly higher age‐adjusted incidence rates in 2014 than women (8.55 per 100 000 [95% CI: 8.42‐8.68] vs 1.65 per 100 000 [95% CI: 1.60‐1.70]; P  < 0.001). A hepatitis C (HCV) birth cohort effect was identified and associated with rapid increases in HCC incidence when members of the cohort aged and entered into age groups 45‐49, 50‐54 and 55‐59. Median survival increased from 2.10 months (95% CI: 1.57‐2.62 months) in those diagnosed between 1982 and 1984 to 12.07 months (95% CI: 11.17‐12.97 months) when diagnosed between 2010 and 2014 ( P  < 0.001). Conclusions: An Australia‐wide analysis of HCC epidemiological trends across three decades shows significant and consistent increases in both incidence and survival. Lay summary: There has been a significant increase in hepatocellular cancer (HCC) reported in Australia over the last three decades without evidence of slowing. Across the same time period, a significant improvement in survival has been identified with the average life expectancy after diagnosis now one year. This research lays the foundation for important public health service delivery.